2022
DOI: 10.1177/15598276221124095
|View full text |Cite
|
Sign up to set email alerts
|

Boxing as an Intervention in Mental Health: A Scoping Review

Abstract: Introduction: Physical activity has been shown to have a multitude of mental health benefits. However, there is limited evidence on the specific mental health benefits of boxing. We conducted a scoping review of academic and grey literature to map research of boxing exercises as an intervention in mental health and to identify gaps in knowledge. Methods: The authors utilized the PRISMA-ScR methodological approach and guidelines from the Joanna Briggs Institute and a structured search was completed from incepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(139 reference statements)
1
1
0
Order By: Relevance
“…Through the psychological scale survey of boxers, it shows that detailed results have been obtained in anxiety level, self-confidence, team identity and opponent attitude, which provides practical data support for boxers' psychological training and psychological support, helps to formulate more personalized and effective training plans and improve athletes' psychological quality in the competition. This is consistent with Bozdarov et al 47 and Donnelly et al 48 .…”
Section: Discussionsupporting
confidence: 91%
“…Through the psychological scale survey of boxers, it shows that detailed results have been obtained in anxiety level, self-confidence, team identity and opponent attitude, which provides practical data support for boxers' psychological training and psychological support, helps to formulate more personalized and effective training plans and improve athletes' psychological quality in the competition. This is consistent with Bozdarov et al 47 and Donnelly et al 48 .…”
Section: Discussionsupporting
confidence: 91%
“…2021 ). For instance, aggressive exercises, including combat sports such as boxing, have been found to offer many benefits, such as improvements in cardiovascular strength, reduce stress, and improve self-confidence ( Wann and Branscombe 1990 ; Bozdarov et al. 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that non-contact boxing drills may be a promising intervention to improve the mental health burden though further well designed randomized controlled trials are needed for confirmation. 11 There is no doubt that boxing instills discipline, character, and confidence. There are numerous boxing programs that help to get kids off the streets, away from crime and drugs.…”
mentioning
confidence: 99%